Exploring tungsten in the environment: geochemical study of an emerging contaminant - Hobson, Chad (Kansas State University, 2013)
Tungsten (W) has become an element of greater concern in recent years. Investigations by the Centers for Disease Control implicated W as a possible link to several cases of childhood acute lymphatic leukemia (ALL) clusters in the western United States. In Fallon NV, 17 cases of ALL were reported from 1997-2001. Previously, it was difficult to attain knowledge about the geochemical behavior of W due to low concentrations and difficulties in detection in natural environments. Modern analytical techniques allow for a greater range of sensitivity, allowing for in depth W analysis. Elucidating information on the factors contributing to the fate and transport of W in low temperature environments will provide insight into how W moves through the environment and provide information to help mitigate W contamination in the future. Three sites were chosen for comparison of W concentration and how that may be linked to local geochemical factors. Fallon NV, Sierra Vista AZ, and Cheyenne Bottoms Refuge KS were chosen based on published literature and personal communications. The objectives for this study were to characterize W concentrations in these three climatologically distinct areas followed by using methods to speciate and semi-quantitatively characterize W phase association within the surficial sediments and using synchrotron X-Ray methods to define W valencies and elemental associations within the sediments. Tungsten occurs in varying concentrations in the study areas, from 17.8 mg/kg to ~25,907 mg/kg. Fallon has the highest average W concentration of the three sites as well as the highest amount of W associated with phases other than the organic matter or residual phase. Speciation of soluble W revealed no polytungstates, however tungstates are present in the samples as well as undefined W species, suggesting there are other forms of W that are readily soluble in water, hence bioavailable. Tungsten has a very heterogeneous distribution in sediments, creating dispersed but highly concentrated clumps of W hotspots. Spot analyses under X-Ray mapping reveal W may co-localize with other metals such as Ti, Co, and Zn.
Keywords: Tungsten; W; Geochemistry; Hobson; Geology (0372)